Sosialisasi Bullying Sekolah Di SMP Muhammadiyah 26 Jakarta Barat - Tiara Yuniar Rizki; Muhammad Iqbal Nana Supriatna; Nuraeni Nuraeni (Panggung Kebaikan : Jurnal Pengabdian Sosial, 2024)
This article aims to educate about the dangers of bullying at school so that it can reduce and prevent bullying cases at school. Bullying is any form of oppression or violence carried out intentionally by one person or group of people who is stronger against another person with the aim of hurting and is carried out continuously. This still happens a lot in the school environment, so the Slipi Complex Group KKN Team held an outreach on the theme of bullying at school. So that school officials, students and students can reduce bullying at school and can follow up on problems experienced by students for the sake of children's mental health. This activity uses a qualitative method using a field study approach. According to Dedy Mulyana, field research is a type of research that studies phenomena in their natural environment, which was held on August 22 2023, targeting students at Muhammadiyah 26 Middle School, West Jakarta.